Push and Pull Factors underlying Agri Enterprise Development in Andhra Pradesh - Deepthi, V; Rambabu, P; Gopikrishna, T (Journal of Agricultural Extension Management, 2018)
The study endeavored to identify the factors which motivated or compelled agripreneurs to establish business enterprises. To this end, 240 agripreneurs comprising both male and female processors, manufacturers, and traders from Chitoor, Krishna and Visakhapatnam districts of Andhra Pradesh were interviewed personally using a pretested interview schedule. The statistics employed for data analysis were Henry Garett’s ranking method. The findings revealed unemployment at rank I, followed by availability of raw material and marketing facilities for the product, insufficient family income and dissatisfaction with salaried job etc. as the push factors. The ability to use previous experience at rank I, followed by family business tradition, desire to be independent and earning more income etc. were identified as the pull factors.